2017
DOI: 10.1177/0148607116671768
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers of Nutrition Support in Critically Ill Trauma Victims

Abstract: In trauma patients requiring 1 or more weeks of intensive care, changes in transthyretin were associated with enteral caloric intake. Our data suggest that transthyretin could be used to monitor nutrition support after 2 weeks in intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 18 publications
2
27
1
2
Order By: Relevance
“…A total of 161 patients with available F-NLR was included in the analysis; 68% were male, with a median age of 62 (range, 52-72) years and a median BMI of 27 (range, [23][24][25][26][27][28][29][30]. Details are listed in Table 1.…”
Section: Baselinementioning
confidence: 99%
See 1 more Smart Citation
“…A total of 161 patients with available F-NLR was included in the analysis; 68% were male, with a median age of 62 (range, 52-72) years and a median BMI of 27 (range, [23][24][25][26][27][28][29][30]. Details are listed in Table 1.…”
Section: Baselinementioning
confidence: 99%
“…Similarly, Parent et al concluded that critically ill trauma patients receiving better adequacy of calories experienced greater changes in transthyretin and serum albumin concentrations after 3 weeks of EN. 26 The Physiologic Impact of EN Several studies have explored the triad of disease/injury, systemic inflammation, and malnourishment. The stress released by disease/injury and metabolism and comorbidities altered by the inflammatory response and malnourishment make the triad highly associated with risk of mortality.…”
Section: Nlr As a Clinical Biomarkermentioning
confidence: 99%
“…We do not assume that these markers correlate with important clinical outcomes; nevertheless, we are encouraged by our observation that early enteral protein supplementation increases visceral protein synthesis. We have previously reported that serum transthyretin concentrations, measured after 2–3 weeks of critical illness, do reflect early nutrition intake and also correlate with clinical outcomes . Although it is therefore reasonable to consider restoration of serum transthyretin concentrations as a surrogate measure of effective nutrition support, we recognize that guidelines do not recommend their use in the management of critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that serum transthyretin concentrations, measured after 2-3 weeks of critical illness, do reflect early nutrition intake and also correlate with clinical outcomes. 10 Although it is therefore reasonable to consider restoration of serum transthyretin concentrations as a surrogate measure of effective nutrition support, we recognize that guidelines do not recommend their use in the management of critically ill patients. Ongoing inflammation, corticosteroid treatment, and organ failure may influence circulating concentrations independently of nutrition support adequacy, and we do not assume our observations are necessarily due to the supplemental protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation